EXTERNAL OFFAL BALI DUCK 26 WEEKS AGES FED RATION WITH FERMENTED PAPAYA LEAF MEAL SUPPLEMENTATION - D. M. R., Prasetia; Siti, N. W.; Sukmawati, N. M. S. (Jurnal Peternakan Tropika; Vol 6 No 2 (2018): May - August 2018, 2018)
This study aims to determine the external offal of bali duck 26 weeks were given feed with fermented papaya leaf meal supplementation has been implemented in the enclosure belonging to Mr. I Ketut Sunatra located at Jalan Bingin Nambe, Kediri, Tabanan. The study was conducted for 14 weeks from September to December 2017 start of preparation until finished. Ducks used are a total of 18 bali ducks with an average initial weight ranges 1286,63 ± 92,88 gram. The experimental design used was a completely randomized design (CRD) which consist of 3 treatments and 3 replications. The treatments were P 0 (ration without supplementation of papaya leaf meal fermented), P 1 (ration with supplementation of 8% papaya leaf meal fermented), and P 2 (ration with supplementation of 16% papaya leaf meal fermented). The variables observed were weight of the head, legs, neck, blood and feathers. The results showed that the ration with fermented papaya leaf meal supplementation did not give a significant effect (P> 0.05) to the weight of the external offal (head, legs, neck, blood and feathers) bali ducks age 26 weeks. Based on these results it can be concluded that supplementation of 8% and 16% flour fermented papaya leaves in ration does not affect the external offal of the bali duck 26 weeks and the ration can be used as an alternative feed ingredient because a cheaper price ration. Keywords: external offal, duck bali, fermented papaya leaf